The impact of collaborative teaching on teaching efficacy among inclusive teachers in Malaysia - Vincent, Jacqueline (Jurnal Pendidikan Bitara UPSI, 2019)
The purpose of this study is to explore the extent of collaborative practices for teaching students with special needs, among mainstream teachers and special needs teachers in Malaysia. Using a qualitative research method, data was generated through focus group sessions with four groups of teachers: pre-service mainstream teachers, in-service mainstream teachers, pre-service special education teachers, and in-service special education teachers. Interview questions were derived from the Teacher Efficacy in Inclusive Practice (TEIP) and the Collaborative Teaching Survey. Through thematic analysis, themes related to collaborative practices and teacher efficacy levels were derived from the participants’ responses. The findings show that although the Malaysian teachers engage in collaborative practices, their perceptions towards students with SEN and their engagement differ according to their roles. Mainstream teachers were found to regard collaboration as seeking advice and exchanging ideas with special education teachers. Special education teachers, on the other hand, suggested that they preferred collaboration in implementing classroom inclusive practices. Interestingly, SEN teachers viewed collaboration with parents as essential to their teaching as well. The findings also suggested that knowledge and experiences in special education influence teachers’ levels of teacher efficacy. The findings of this study support the cruciality of collaborative practices as a means of resolving issues of inadequate resources for students with special or additional needs in the Malaysian classrooms.